Caracterização genética e evolução dos vírus dengue no Estado do Rio Grande do Norte - Sousa, Denise Maria Cunha de (2014)
Dengue is considered as the most important arthropod-borne viral disease throughout the world due to the high number of people at risk to be infected, mainly in tropical and subtropical regions of the planet. The etiologic agent is Dengue Virus (DENV), it is a single positive-stranded RNA virus of the family Flavivirus, genus Flaviviridae. Four serotypes are known, DENV-1, DENV-2, DENV-3 and DENV-4. One of the most important characteristic of these viruses is the genetic variability, which demands phylogenetic and evolutionary studies to understand key aspects like: epidemiology, virulence, migration patterns and antigenic characteristics. The objective of this study is the genetic characterization of dengue viruses circulating in the state of Rio Grande does Norte from January 2010 to December 2012. The complete E gene (1485 pb) of DENV1, 2 e 4 from Brazilian (Rio Grande do Norte) patients was sequenced. Phylogenetic analysis was performed using MEGA 5.2 software, Tamura-Nei model and Neighbor-Joining trees were inferred for the datasets. In Brazil, there is just one DENV-1 genotype (genotype V), one DENV-2 genotype (Asian/American) and two DENV-4 genotypes (genotypes I and II). Brazilian strains of DENV-1 are subdivided in two different lineages (BR-I and BR-II), the Brazilian strains of DENV-2 are subdivided in four lineages (BRI-IV) and genotype II of DENV-4 is subdivided in three Brazilian lineages (BRI-III). The viruses isolated in RN belong to lineage BR-II (DENV-1), BR-IV (DENV-2) and BR-III (DENV-4).The Caribbean and near Latin American countries are the main source of these viruses to Brazil. Amino acids substitutions were detected in three domains of E protein, this makes clear the necessity of studies that associate epidemiological and molecular data to better understand the effects of these mutations. This is the first study about genetic characterization and evolution of Dengue viruses in Rio Grande do Norte, Brazil